School in Rurality: Review About Inclusion in Education - Vargas, Yaneth Clementina; Romero Alfonso, Sonia Lucia (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The article presents the results of a review paper about research related to inclusion processes in rural education. There are trends, according to Michel Foucault, genealogy. Based on the research references, we analyzed the implications on the evolution of educational inclusion in rural contexts of different countries to highlight practices and particular discourses. This text can be a reference for research processes on the problems that mark inclusive education in Colombia.